Combination of Niclosamide and Pirfenidone Alleviates Pulmonary Fibrosis by Inhibiting Oxidative Stress and MAPK/Nf-κB and STATs Regulated Genes - Hanaa Wanas; Hossein M. Elbadawy; Mohannad A. Almikhlafi; Amany E. Hamoud; Eid N. Ali; Amr M. Galal (MDPI AG, 2023)
The pathogenesis of pulmonary fibrosis (PF) is extremely complex and involves numerous intersecting pathways. The successful management of PF may require combining multiple agents. There is a growing body of evidence that suggests the potential benefits of niclosamide (NCL), an FDA-approved anthelminthic drug, in targeting different fibrogenesis molecules. This study aimed at investigating the anti-fibrotic potential of NCL alone and in combination with pirfenidone (PRF), an approved drug for PF, in a bleomycin (BLM) induced PF experimental model. PF was induced in rats by intratracheal BLM administration. The effect of NCL and PRF individually and in combination on different histological and biochemical parameters of fibrosis was investigated. Results revealed that NCL and PRF individually and in combination alleviated the histopathological changes, extracellular matrix deposition and myofibroblastic activation induced by BLM. NCL and PRF either individually or in combination inhibited the oxidative stress and subsequent pathways. They modulated the process of fibrogenesis by inhibiting MAPK/NF-κB and downstream cytokines. They inhibited STATs and downstream survival-related genes including BCL-2, VEGF, HIF-α and IL-6. Combining both drugs showed significant improvement in the tested markers in comparison to the monotherapy. NCL, therefore, has a potential synergistic effect with PRF in reducing the severity of PF.